Prevalence of dental caries based on personality types of 35-44 years old residents in Davangere city - Puja C. Yavagal; Hitashi Singla (Elsevier, 2017)
Aim: To assess dental caries experience of different personality types of 35-44 years old residents in Davangere city. Materials and methods: A cross-sectional survey was conducted in field setting. Based on Jenkins Activity Survey Questionnaire11 used to assess the personality types, a personality questionnaire was designed consisting of 20 items. Questionnaire was used to assess and categorize personality types as Type A, Type B and Type AB. Data were analyzed using SPSS software version 17. Standard descriptive statistics were generated. Evaluation of data was done using chi square test. Results: Prevalence of dental caries was 96.6% in Type A personality and 95.9% in Type B personality and this difference was not statistically significant (person chi square p value = 0.53). Discussion: In a cross-sectional survey it is difficult to inspect personality types which is a qualitative variable with some people giving different responses at different occasions. There are chances of social desirability bias. Hence, longitudinal studies should be conducted to ascertain the association between personality types and dental carries.